3-Benzyl-6-bromo-2-(2-furyl)-3H-imidazo[4,5-b]pyridine - Ouzidan, Y.; Rodi, Y.K.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title molecule, C(17)H(12)BrN(3)O, the imidazopyridine ring system is almost coplanar with the furan ring [dihedral angle = 2.0 (3)degrees]. The benzyl phenyl ring is oriented at dihedral angles of 85.2 (2) and 85.5 (1)degrees, respectively, with respect to the furan ring and the imidazopyridine ring system. In the crystal, molecules are linked into chains propagating along the b axis by C-H center dot center dot center dot N hydrogen bonds. Adjacent chains are linked via short Br center dot center dot center dot Br contacts [3.493 (1) angstrom].